A qualitative investigation on the successful turnaround strategy from top leader perspectives: Examples from Indonesia - Yulihasri; Arief Prima Johan; Rebi Fara Handika; Herri (Verslas: Teorija ir praktika / Business: Theory and Practice, 2018)
Turnaround process involved many approaches of strategic and tactical attempts. However, such knowledge are difficult to identified since many previous studies only focused on what constitute successful turnaround, and limited to the use of financial data. As turnaround is a transformational process comprehend every element of organization, ploy on implementing and orchestrating such strategic action should be determined by company's top leaders. The purpose of this study was to explore the way in which leaders manage the company's turnaround process and their leadership style through a qualitative study in Indonesian business. Drawing from several top managers in various industry in Indonesia, the result showed that there are many attempt should consider on implementing turnaround process. Financial restructuration, employee's transformation initiative, and business reengineering process are imperative approaches. Furthermore, leaders need to consider top-down approach on decision making, attention to detail, and open communication to gain employees commitment.
Keywords: M12; M14; 650; turnaround strategy; transformational process; strategic leadership; top leaders; qualitative method